2022
DOI: 10.1039/d2cc03831e
|View full text |Cite
|
Sign up to set email alerts
|

Translating solution to solid phase glycosylation conditions

Abstract: Optimizing glycosylation conditions for automated glycan assembly is highly challenging, demand wasteful use of precious building blocks and rely on nontrivial analyses. We developed a semi-quantitative method for automated optimization...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…44–46; for glycans see: ref. 22, 24 and 32; Bakhatan et al 32 recently reported dimer formation with a cycle time of 8 min).…”
Section: Solid Phase Synthesis (Sps)mentioning
confidence: 97%
See 3 more Smart Citations
“…44–46; for glycans see: ref. 22, 24 and 32; Bakhatan et al 32 recently reported dimer formation with a cycle time of 8 min).…”
Section: Solid Phase Synthesis (Sps)mentioning
confidence: 97%
“…Film diffusion resistance may be minimal on particle sizes of 35-100 μm". 54 32 recently reported dimer formation with a cycle time of 8 min). c Obtained from equipment manufacturers (taking the upper limit).…”
Section: Momentum Transfer: Mixing In Spsmentioning
confidence: 98%
See 2 more Smart Citations
“…Semi-automated temperature-controlled experiments aid in selecting reaction temperatures for thioglycoside building blocks to be used in AGA synthesisers. 32,33 Identification of the optimal reaction temperature drastically improves the efficiency of AGA processes, as illustrated in the context of a β-(1-4) glucan synthesis. 32 Activation experiments with glycosyl phosphates, in the absence of a nucleophile, at different temperatures were carried out in the AGA reactor (Table 1).…”
mentioning
confidence: 99%